GAMBARAN TINGKAT KECEMASAN PADA WANITA USIA SUBUR YANG MENGALAMI INFERTILITAS - Diana, Alis Nur; Firdaus, Nailufar (NHM PRESS, 2023)
There are many worry of healthy age couple like mentally interference, Think of surroundings. So the problem of this analysis is still many healthyage couple that have worry because of infertilation. The goal of this research is for to know the worry level to healthy age couple that under go infertilation. Study in BPS kun Indari S,ST pamekasan 2017. This research use descriptive design. Variable in This research is worry level to healthy age couple that under go infertilation, Population account is 12 by technic sampling that’s used in this research is total sampling. The data is collected by quisioner and interview. From the reseach show that almost all of the healthy age couple under go worry in BPS Kun Indari S,ST. From 12 respondent, 3 respondent (25%) have medium worry, while 9 respondent (75%) have high worry. The effort that can do by midwifery and health staff is give concelling how healthy live habit keep eating system. The bad things in our society are like pack maetball in hot condition with plastic. The monomer donger for health if it consume. For woman, the tight clouth can appear fungus, whitish and itch to feminity organ. And it can interfere healthy to healthy age couple. Give social support, spiritual and also give family support for healthy age couple so that the worry can be overcome. .